Cyberbullying Against Queer People on Social Media: A Study Based on Facebook - Anutharsi, G.; Poongulaly, S. (University of Jaffna, 2022)
Media images help to shape the view of the world and play a major role in the society. In the modern society, new media plays an inevitable part in the human communication. Accordingly, social media like Facebook, Twitter, WhatsApp, Instagram, TikTok and other similar social media are playing an eminent role in the contemporary period in conveying the messages to the public. Further, social media create positive and negative impact among people, especially in a marginalized community. The objectives of the study are: to identify the cyberbullying against LGBTIQA+ (Lesbian, Gay, Bi sexual, Transgender, Inter sex, Queer, and Asexual) people on Social Media in Jaffna region and to find out the impact of the cyberbullying faced by LGBTIQA+ people on Social Media. Qualitative methodology & quantitative have been used for the analysis. Primary and secondary data are used for this study. The observation method, survey method and in-depth interview have been applied in terms of primary data throughout the study. The study is limited to Facebook in social media platform. Totally, 35 Queer people and 15 Queer activists interviewed for the study. This study explains the theoretical platforms to reveal the significant value of the research. Queer theory express the rights of people. The finding of the study indicates that LGBTIQA+ people experienced difference form of online violence on Social Media. The cyberbullying and hate speech impact them in major level. Transgender people are accepted by the community to some extent. Even though, most probably LGBTIQA+ people face challenges on social media and the cyber violence they are facing through social media have an impact in their life in a cruel manner in many ways. Psychological abuse, verbal harassment, bullying, mobbing, cyber harassment, sexual exploitation, sexual assaults, revenge porn, trolling, and identity theft are faced by queer people via social media in Jaffna.
Keywords: Cyberbullying; Impact; LGBTIQA+; Queer; Social Media